Electric Conductivity of Cured Arylhydrazino-N,N’-(4,4’,1,1’-Sulfonyl Biphenylene) Bis-Maleimide-Epoxy Resins - Patel, S.V.; Daraji, J.M.; Patel, J.C. (Asian Journal of Chemistry, 2016)
Arylbydrazino-bismaleimide (AHBM) have been prepared by the Michael addition reaction of various phenyl hydrazine derivatives with N,N'-(4,4'-1,1'-sulfonyl biphenylene) bis-maleimide (SBM). These arylhydrazino bismaleimides (AHBM) were employed for curing commercial epoxy resins. The curing behaviour of commercial epoxy resin with these AHBM compounds using 2-methyl imidazole as a catalyst has been monitored using differential scanning calorimetry. Glass fibre reinforced composites of the epoxy-AHBM system have also been prepared and characterized mechanically and chemically. The electrical conductivity of all unreinforced epoxy-AHBM cured products were measured at room temperature and it was found that the produced cured materials having good chemical resistance, good mechanical strength and low conductivity.